Applying Global Models of Teacher Development to Improve Student Outcomes: Insights from a Teacher Development & Leadership Program in Qatar - Seungah S. Lee; Leena Zahir (Gulf Education and Social Policy Review)
Abstract This paper aims to examine the relationship between progressive teaching practice and student academic and non-academic outcomes. The teacher development and leadership (TDL) program is a Qatari teacher development program that is a part of a wider global network (called “Global Network”) that aims to expand educational opportunities through teacher development with its roots in the United States. (Names of organizations have been changed for anonymity). The training model of TDL program is based on six themes: (1) orientation to student vision, (2) ongoing reflection to improve practice, (3) setting high expectations for students, (4) ensuring content rigor and mastery in students, (5) fostering positive culture and learning environment, and (6) building positive relationships with students. We used a dataset that includes aggregate student- and teacher-level data from 136 classrooms (with 2,087 students) of 41 teachers between 2015 and 2017 to understand the relationship between teacher effectiveness and student outcomes. We found that establishing a positive rapport with students, practicing ongoing reflection, and internalizing learning are associated with higher academic achievement. We also found that incorporation of student vision for teaching practice is correlated with students having more positive attitude toward learning.